Blockchain-based electronic Bill of lading : Potentials and Challenges - Nguyen, Ha Mi (2024)
The aim of this bachelor’s thesis is to evaluate aspects of an electronic bill of lading based on blockchain technology with a focus on its differences from a traditional bill of lading in paper form. This thesis aims to evaluate its potential benefits and challenges for companies to adopt in international trade while also giving insights into an example of a current practical implementation of the blockchain technology in context with electronic bill of lading such as FIATA e-FBL.